School-based abuse prevention for children with communicative and/or cognitive disabilities : guidelines for program implementation - Bornman, Juan, 1968- (University of Pretoria, 2022)
Thesis (PhD (Augmentative and Alternative Communication))--University of Pretoria, 2021.